Increasing students grammar learning motivation through consciousness-raising tasks: communicative English skills I - Gobena, Gadisa Tadesse (Journal of Education, Society & Multiculturalism (Online), 2022)
The purpose of this study was to assess students’ grammar learning motivation through consciousness-raising tasks. To this end, the descriptive survey was carried out through a questionnaire and focus group discussion (FGD). The data gathered from the questionnaire was analyzed using descriptive statistics such as frequency, percentage, and mean. This study was encouraged to take a sample of freshmen students from the limited sections. From these, 92 students participated. The study revealed that students were reluctant to practice their grammar on their own practice. On the other hand, the contents of the course itself do not allow students to do better without the help of teachers, as it does not include all the activities that push students to do well on their own. In addition, the teacher rarely encourages students to acquire additional grammar rules to develop a language without being aware of it during the lesson.